Characteristics and Hospital Costs of Spica Cast Treatment of Non–accidental-related Diaphyseal Femoral Fractures in Children Before Walking Age. Issue 10 (November 2020) - Magee, Lacey C.; Mahmoud, Mahmoud A.H.; Baldwin, Keith; Talwar, Divya; Gandhi, Jigar S.; Arkader, Alexandre
Abstract : Background: Fractures are one of the most common presentations of child abuse second only to soft tissue damage, with ∼60% of fractures being femur, humerus or tibia fractures. Although studies have shown increased health care costs associated with nonaccidental trauma (NAT), there is little data regarding the cost of NAT-associated fractures compared with accidental trauma (AT) related fractures. The purpose of this study was to consider the economic burden of NAT related femoral fractures compared with AT femoral fractures. Methods: We performed a retrospective study of children under the age of one with femoral fractures treated with a spica cast at a Level 1 Pediatric Trauma Center between 2007 and 2016. Variables included age, sex, length of hospital stay, and estimated total billing cost obtained from this hospital's billing department. In addition, fracture site (mid-shaft, distal, proximal, and subtrochanteric) and pattern were assessed. Results: Sixty children with a mean age of 7 months were analyzed. NAT was suspected in 19 cases (31.7%) and confirmed in 9 (15%) before discharge. Two groups were analyzed: the NAT group included suspected and confirmed cases of abuse (28) and the AT group contained the remaining 32 cases. There was no significant difference in the demographics between these 2 groups. Children in NAT group had a longer length of stay compared with AT group (78.9 vs. 36.7 h, P <0.001). Overall consumer price index-adjusted hospital costs were 24, 726 higher for NAT group compared with AT group ( P =0.024), with costs of laboratory workup, radiology, and nonorthopaedic physician fees being the top 3 components contributing to the increased costs. Conclusions: The overall incidence of NAT was 46.6% in children presenting with femoral fracture under 1 year of age. The overall hospital cost of treating fractures in the NAT group was 1.5 times higher than the AT group, with imaging charges the most significant contributor to cost difference. Level of Evidence: Level III—retrospective review.